In-situ laser-ultrasonic visualization with the use of regenerated fiber Bragg grating sensors at elevated temperatures. (1st April 2023) - Li, Zixuan; Yu, Fengming; Saito, Osamu; Okabe, Yoji
Abstract: The authors have developed a high-temperature ultrasonic sensing system with a regenerated fiber Bragg grating (RFBG) sensor, that was fabricated by annealing a fiber-optic Bragg grating (FBG). Different from the common FBG, the RFBG ultrasonic sensor is resistant to temperature as high as 900 °C. In this study, taking advantage of the RFBG sensor, we attempted to establish a laser-ultrasonic visualization method for in-situ damage diagnosis in heat-resistant materials at elevated temperatures. In the first part of this paper, after reporting the fabrication of the RFBG in detail, we validated that the RFBG sensor has reasonable sensitivity to ultrasonic measurement over a broad frequency range at high temperatures. The RFBG was then incorporated into a laser-ultrasonic visualizing inspector to visualize the ultrasonic wave propagating in a SiC plate with an artificial defect at 800 °C. An improved data processing method was employed to verify the reliability of the visualization result. In the processing method, the visualization result was transformed to the spectrum in the wavenumber-frequency domain with the help of three-dimensional fast Fourier transform. Referring to theoretically calculated dispersion curves of the Lamb wave propagating in the SiC plate, we identified S0 and A0 modes from the spectral results. In addition, the agreement between the theoretical results and the experimental results also verified the feasibility of our proposed system to visualize the ultrasonic wavefield in high-temperature environment. Moreover, we developed a window function to extract the wave modes from the visualization result based on the dispersion curves. The artificial defect in the SiC plate could be then clearly localized from the visualization results for the separated individual modes.